(untitled) (Fiep Bulletin - online, 2011)
In order to assess possible changes in blood after physical exercise sessions in the use of testosterone, 12 Wistar rats groups underwent 20 sessions of swimming with daily training sessions of 40 minutes 5 times a week after two weeks of adaptation to an overload of 5% body weight attached to its tail. Their animals were divided into two groups: trained control group (C) and control treated (T), where the treated group than in the sessions of swimming, was applied 15mg/kg-1 (the value of their body weight) of durateston ® twice a week and control groups had undergone similar but were injected with oil peanuts. On the last day of 4 weeks of training the animals were undergoing a training period until exhaustion, sedo from water, dried, injected with ketamine and xelasina for later beheaded by guillotine for blood tests. The analysis showed the control group (C), the lowest glucose exhaustion after (92.75 ± 14.05 mg / dL) and pre-exercise (42 ± 12.24 mg / dL) after exercise, but this same group was found the lowest lactate post depleted (7.32 ± 3.12 mmol / L), also in control animals the swimming time was 203.75 ± 71.92 minutes. The control group treated (T) had higher post-exercise blood glucose value (73.4 ± 39.87 mg / dL), lactate (9.28 ± 2.67 mmol / L) and swimming time (305.8 ± 34.36 minutes) leading us to believe that the use of injectable testosterone in older animals increases their athletic performance and leads to better glycemic control, which may be explained by the longer duration of exercise performed by these animals in the group treated with hormone , which was significantly higher good.